2021
DOI: 10.1088/1748-605x/abd051
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and wound healing effect of alginate/chitosan microcapsules loaded with polysaccharides from Nostoc Commune Vaucher

Abstract: Biologically active coating materials could promote the growth of granulation tissue as auxiliary materials, while natural polysaccharides could promote vascular regeneration and wound healing. Therefore, in this study, ultrasound-assisted extract of Nostoc commune Vaucher polysaccharides (UAP) yield after the process optimization was 12.89 ± 0.24%, which was used to prepare microcapsules by emulsification and cross-linking. The effect of alginate/chitosan-UAP composite materials on wound healing in an experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Conversely, free radical mediated cellular damage marker (LPO) were significantly reduced in EGTE groups, apparently significant reduction of LPO levels is an important indication of free radical scavenging activity of EGTE, which ameliorates oxidative damage and henceforth modulates inflammation which plays an important role in wound healing. There are some earlier studies that have reported free radical scavenging activity of crude earthworm tissue extracts, earthworm coelomic fluid extracts and other preparations derived from earthworms, hence based on results of present study it can be postulated that EGTE provides protection to cells and cellular macromolecules under oxidative stress conditions [ 51 ]. Researchers have found that free radicals in tissue micro-environment are involved in delayed wound healing in diabetic patients, hence amelioration of oxidative stress by EGTE protect cells from pathological changes initiated by free radicals [ 52 ].…”
Section: Discussionmentioning
confidence: 64%
“…Conversely, free radical mediated cellular damage marker (LPO) were significantly reduced in EGTE groups, apparently significant reduction of LPO levels is an important indication of free radical scavenging activity of EGTE, which ameliorates oxidative damage and henceforth modulates inflammation which plays an important role in wound healing. There are some earlier studies that have reported free radical scavenging activity of crude earthworm tissue extracts, earthworm coelomic fluid extracts and other preparations derived from earthworms, hence based on results of present study it can be postulated that EGTE provides protection to cells and cellular macromolecules under oxidative stress conditions [ 51 ]. Researchers have found that free radicals in tissue micro-environment are involved in delayed wound healing in diabetic patients, hence amelioration of oxidative stress by EGTE protect cells from pathological changes initiated by free radicals [ 52 ].…”
Section: Discussionmentioning
confidence: 64%
“…has the anticancer activity, 14 hypoglycemic effect, 15 and wound healing ability. 16 Our previous study also had found that N. commune Vauch. polysaccharide (NCVP) is beneficial to maintain the gut health.…”
Section: Introductionmentioning
confidence: 82%
“…Polysaccharide as the main components of N. commune Vauch. has the anticancer activity, 14 hypoglycemic effect, 15 and wound healing ability 16 . Our previous study also had found that N. commune Vauch.…”
Section: Introductionmentioning
confidence: 87%
“…The dispersion and microstructure of the microcapsules were observed by TEM (TEM-1200EX, JEOL Corporation, Japan) [38,39] 2.5.9. Mechanical property test of CPNP microcapsules According to the reference outlined method [40].…”
Section: Scanning Electron Microscope (Sem) and Transmission Electron...mentioning
confidence: 99%